PERANAN MUHADHARAH DALAM MENINGKATKAN SKIL CERAMAH SISWA SMP INSAN KAMIL ISLAMIC SCHOOL KOTA BENGKULU - Risna Dewi; Nazar; Siti Misbah (JOISCOM (Journal of Islamic Communication), 2024)
ABSTRACT This study aims to determine the implementation of muhadharah activities at Insan Kamil Islamic Junior High School of Bengkulu City. What is the role of muhadharah activities in improving students’ lecture skiils of Insan Kamil School. The results of this study conclude that (1) the implementation of muhadharah is mandatory for all student, carried out in groups routinely every Friday after doing maghrib prayer. The implementation process starts from writing texts, memorizing, and delivering speeches. The agenda are: opening, reciting, the holly Qor’an and sholawat, main events, closing, and others. The rules for this activity include the regulations before and during the implementation. In this activity there is punishment (standing) and rewards (money and notebooks). The research method used in this study was descriptive qualitative research. The data collection techniques were trhough the observation, interviews, and documentation. The data sources were the primary data and the secondary data sources. Based on the results of the research it can be found that the muhdharah activities carried out at Insan Kamil Islamic School are not only giving speeches but using rules of conduct, events with MCs, reading the Qor’an, taking the core material by all the participants and also there is an entertainment. The muhadharah avtivities at Insan Kamil Islamic School are very helpful in developing the self-potential possessed by Insan Kamil Islamic Junior High School students in developing the lecture skills in front of friends and public, and training the students’ mentality. Keywords:Muhadharah, Improving, Lectur